PROFILE OF CHILDREN WITH PRE READING DIFFICULTY (Proceedings of International Conference on Special Education, 2022)
This research is a qualitative research aiming at understanding the profile of children who have impairment in pre- reading development area applied in three kindergartens in Bandung with 37 children as subjects. The method implemented is a test on prereading abilitywhich is pictured in 6 aspects of pre-reading ability, namely: 1) oral language development; 2) concept about print; 3) alphabet knowledge ; 4) phonemic awareness; 5) letter-sound correspondence and 6) beginning reading vocabulary, observation and interview are also accomplished other than the test to further picture the children’s profile. The result of the test shows there are 12 children with impairment in pre-reading ability, with the most problems as follow: 92.3% having impairment in letter-sound correspondence, 84.6% with impairment in beginning reading vocabulary, 69.2% having impairment in alphabet knowledge, 61% having disabilityin oral language development and 38,4% having impairment in concept about print. In the second phase of the research it is found out that among the 12 childrenwith pre-reading difficulties there are 10 children who have impairment in linguistic awareness and 6 children having problem with visual perception. The result of observation and interview show that there more children with pre-reading difficulties in schools with minimum learning facilities and parents with less concern about their children’s learning problems and impairment.